Effect of diet counseling on knowledge, attitude and practice and quality of life of diabetic patients in Kuantan, Malaysia - Anuar, Nurfarhana Ezzaity; A. Rahman, Nor Azlina; Mohamed Nor, Noraishah; A.Rahman, Nor Iza; Haque, Mainul (Malaysian Society for Pharmacoeconomics and Outcome Research, 2016)
This research was intended to assess the impact of dietary counseling for diabetic patients. By giving the advice to control the blood sugar, does it improve the wellness of the diabetic patients? This research was conducted from January until December 2011 with the aim to study the factors associated with knowledge, attitude and practice (KAP) and quality of life (QOL) of type 2 diabetic patients, and the effect of dietary counseling on their KAP and QOL. A total of 63 respondents were involved in this intervention study, including 31 respondents from the intervention group and 32 respondents from the control group. The intervention group was selected by purposive sampling based on doctor’s referral for diet counseling of the respondents, while a convenience sampling method was used for the control group. Based on the baseline results of both groups, a significant correlation was found between knowledge with duration of having DM (p=0.019) and race (p=0.002). Race and educational level were found to have significant correlation with attitude where the p=0.001 and p=0.037, respectively. Significant difference was only found in race for practice scores (p=0.019). There was a significant correlation found between QOL and age (p=0.031). Further analysis comparing the pre and post intervention result shows that the total scores for KAP and QOL in the intervention group was improved after the diet counseling given, as compared to the control group, but the difference was not significant statistically. In conclusion, better methods might need to be developed for more effective health education and counseling to better improve diabetic patients’ KAP and QOL, thus reducing the complications of the disease.